2017
DOI: 10.7324/japs.2017.70401
|View full text |Cite
|
Sign up to set email alerts
|

Modulatory effect of berberine on adipose tissue PPARγ, adipocytokines and oxidative stress in high fat diet/ streptozotocin-induced diabetic rats

Abstract: The current study was designed to investigate the anti-hyperglycemic and antioxidant effects of berberine (BBR) in high fat diet/streptozotocin (HFD/STZ)-induced type 2 diabetic rats, focusing on the role of adipose tissue peroxisome proliferator activated receptor gamma (PPARγ), resistin and inflammatory cytokines. Type 2 diabetes was induced by feeding rats with HFD for 4 weeks followed by a single intraperitoneal injection of 35 mg/kg body weight STZ. Diabetic rats were supplemented with 50 and 100 mg/kg BB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 34 publications
(41 reference statements)
2
6
0
Order By: Relevance
“…Thus, Ber promoted IVM of porcine oocytes and the development of IVF embryos. Studies have shown that feeding Ber to obese rats decreased transcription of PPARG in the adipose tissue of rats (Ayman et al, 2017) and decreased phosphorylation of JNK in ileal cells of rats (Cui et al, 2018), which is consistent with our results.…”
Section: Discussionsupporting
confidence: 93%
“…Thus, Ber promoted IVM of porcine oocytes and the development of IVF embryos. Studies have shown that feeding Ber to obese rats decreased transcription of PPARG in the adipose tissue of rats (Ayman et al, 2017) and decreased phosphorylation of JNK in ileal cells of rats (Cui et al, 2018), which is consistent with our results.…”
Section: Discussionsupporting
confidence: 93%
“…Improvements in blood glucose levels after the intervention with LVSP and AST also have an impact in improving metabolism, marked by a decrease in the activity of glucose-6-phosphatase and fructose-1-6-bisphosphatase, which participate in glucose formation and decrease gluconeogenesis that has previously occurred in T2DM. The reduction of tissue protein disassembly as a raw material for gluconeogenesis results in improvement of weight gain and insulin sensitivity (Pournaghi et al , 2012; Mahmoud et al , 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown an increase in NO levels in patients with diabetes mellitus [ 231 ]. Berberine has been reported to reduce NO levels [ 196 , 205 ]. Under hyperglycemic conditions, NO levels increase through the upregulation of iNOS.…”
Section: Antioxidant Activity Of Berberinementioning
confidence: 99%